Factors associated to labour absenteeism due to medical cause in an university institution - Juan F. Saldarriaga; Elkin Martínez L (Universidad de Antioquia, 2007)
Labor absenteeism due to medical cause has unfavorable implications for everybody. The employee suffers with the disease, the company loses productivity and society suffers delays in its economical and social growth. The study of this problem is obviously necessary in order to achieve an appropriate prevention and control of it. Objective: to explore the behavior of absenteeism by medical causes and its associated factors among the afﬁliates to the health program in the University of Antioquia, Colombia. Methods: frequency, duration, costs and causes of absenteeism are studied in relation to sex, age and physical activity as a regular behavior. Relative risk and its 95% conﬁdence intervals are estimated. Results: respiratory diseases are the ﬁrst cause of labor medical handicap. Absenteeism is higher in women. RR 1.65 (CI 95% 1.53-1.77). It has a close relationship to age RR 1.25 (CI 95% 1.12-1.38) and to sedentariness RR 2.17 (IC 95% 1.72-2.73).